Web-based accountability and sustainability in China's charitable foundations / Zhang Xun - Zhang , Xun (2023)
Nonprofit organizations (NPOs) are important for the public and are deemed to functionalize as complementary to government organizations. Due to the nonprofit characteristics, financial sustainability and social sustainability issues have been encountered by NPOs. According to the stakeholder theory, financial sustainability and social sustainability could be improved through effective accountability. However, as the most important NPOs in China, foundations have been troubled by continuous scandals, and their sustainability is greatly diminished. To regain public confidence and credibility, foundations need to ensure accountability towards the requirements of the public. With the rapid development of the Internet in China, web-based accountability provides advantages, such as higher accessibility and lower cost. In this study, the associations between web-based accountability and sustainability in Chinese NPOs were investigated. Using the quantitative approach, secondary data were analyzed through a multiple regression model. The findings suggest that the sustainability of China foundations is positively associated with web-based accountability. Specifically, financial and social sustainability could be affected by both information disclosure and dialogue communication. Notably, interactive engagement, as one special kind of dialogue communication under a web-based environment, shows a significant positive influence on foundations' sustainability. Overall, the findings of this study contribute theoretically to fulfill several research gaps, and provide practical instructions to various parties, such as governors and regulators, managers, financiers, and the public.